E-rational voters: measuring the effects of internet and media freedom on the political budget cycle in a weak democracy. - Martínez Torres, Hans Yoel (2017)
This paper studies the effects of internet access and media freedom on the electoral outcomes in 31 Mexican states during governor elections between 1999 and 2015, by testing assumptions of the Political Budget Cycle (PBC) theory. Previous studies in Mexico have missed to consider the role of voters. Evidence suggests that: 1) Expansive expenditure growth during the year before elections increases incumbent party’s vote share, and 2) On the contrary, an increase in the portion of the population that has access to internet reduces incumbent party’s vote share. Both results seem to coexist even after controlling by economic performance and making estimations robust to time and education effects. Furthermore, the expenditure effect seems to decrease as more people have access to internet. Finally, opposite to a previous study, evidence suggests that PBC does pay off in Mexico.